ANALISIS EFEKTIVITAS, KONTRIBUSI DAN POTENSI PAJAK KENDARAAN BERMOTOR SEBAGAI SUMBER PENDAPATAN ASLI DAERAH DI PROVINSI SULAWESI UTARA - Kansil, Tiara A. M.; Kalangi, Lintje; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Motor Vehicle Tax is a regional tax that been collected and managed by the provincial government which is expected to increase the revenue of Local Original Income. The purpose of this research is to find out the effectiveness ofÂ  Motor Vehicle Tax revenue is, also to find out contribution that Motor Vehicle Tax has given to Local Original Income, and to see the potential of Motor Vehicle Tax itself. The type of research used in this study is descriptive, where all the data obtained will be explained one by one and then will be analyzed, so that we can find out the conclusion that can answer the main purpose of this research. The results of this research indicate that revenues of Motor Vehicle Tax for the fiscal year 2014 to 2017 has been very effective. The contribution of Motor Vehicle Tax to Local Original Income from 2014 to 2017 ranged between 25%-30% which means that was a quarter of the local income. Motor Vehicle Tax has great potential, which is about 45,03% to be developed by the regional government.Keywords: Effectiveness, Contribution, Potency, Motor Vehicle Tax, Local Original Income